LRP5 Regulates Human Body Fat Distribution by Modulating Adipose Progenitor Biology in a Dose- and Depot-Specific Fashion - Loh, Nellie Y.; Neville, Matt J.; Marinou, Kyriakoula; Hardcastle, Sarah A.; Fielding, Barbara A.; Duncan, Emma L.; McCarthy, Mark I.; Tobias, Jonathan H.; Gregson, Celia L.; Karpe, Fredrik; Christodoulides, Constantinos (Cell metabolism, 2015)
Common variants in WNT pathway genes have been associated with bone mass and fat distribution, the latter predicting diabetes and cardiovascular disease risk. Rare mutations in the WNT co-receptors LRP5 and LRP6 are similarly associated with bone and cardiometabolic disorders. We investigated the role of LRP5 in human adipose tissue. Subjects with gain-of-function LRP5 mutations and high bone mass had enhanced lower-body fat accumulation. Reciprocally, a low bone mineral density-associated common LRP5 allele correlated with increased abdominal adiposity. Ex vivo LRP5 expression was higher in abdominal versus gluteal adipocyte progenitors. Equivalent knockdown of LRP5 in both progenitor types dose-dependently impaired β-catenin signaling and led to distinct biological outcomes: diminished gluteal and enhanced abdominal adipogenesis. These data highlight how depot differences in WNT/β-catenin pathway activity modulate human fat distribution via effects on adipocyte progenitor biology. They also identify LRP5 as a potential pharmacologic target for the treatment of cardiometabolic disorders. [Display omitted] •Carriers of LRP5 variants display altered body fat distribution•LRP5 is more highly expressed in abdominal versus gluteal fat progenitor cells•LRP5 knockdown in both progenitor types leads to different biological responses•LRP5 modulates fat progenitor biology by controlling β-catenin signaling dosage Loh et al. identify the WNT co-receptor LRP5 as a regulator of human body fat distribution, an independent predictor of diabetes and cardiovascular disease risk. Studying LRP5 gene variant carriers and human fat progenitors, they show that LRP5 differentially modulates regional adipose progenitor biology by titrating WNT/β-catenin signaling dosage.